Evaluasi Sistem Akuntansi Penjualan Kredit, Piutang dan Penerimaan Kas Pada PT. Insan Media Pratama - Vini Mariani; Sintha Permatasari (Bina Nusantara University, 2011)
Credit sales in a company have greater risks than cash sales do. An excellent internal control is needed over the accounting system of credit sales, receivables and cash receipts to reduce the occurrence of these risks. This study aims to evaluate, identify weaknesses and limitations of internal control and suggests some improvements as needed. The methods used are literary study on books, textbook, and other related literatures; field research by interviewing the relevant parts and observing the company activities, forms and accounting records used.